2023
DOI: 10.3389/ffgc.2023.1152142
|View full text |Cite
|
Sign up to set email alerts
|

Increase in fine root biomass enhances root exudation by long-term soil warming in a temperate forest

Jakob Heinzle,
Xiaofei Liu,
Ye Tian
et al.

Abstract: Trees can invest up to one-third of the carbon (C) fixed by photosynthesis into belowground allocation, including fine root exudation into the rhizosphere. It is still unclear how climate and soil warming affect tree root C exudation, in particular quantifying longer-term warming effects remains a challenge. In this study, using a C-free cuvette incubation method, in situ C exudation rates from tree fine roots of a mature spruce dominated temperate forest were measured in regular intervals during the 14th and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 67 publications
0
5
0
Order By: Relevance
“…For example, the turnover rate of the amino sugars was found to be faster under elevated CO 2 (Glaser et al, 2006). Secondly, our previous studies have confirmed enhanced plant root C input in warming plots, due to increased root growth/turnover and root exudation (Heinzle et al, 2023;Kengdo et al, 2022Kengdo et al, , 2023, indicating a shift in the balance of plant-versus microbial-derived SOM under climate warming.…”
Section: Warming Reduced the Microbial Necromass Carbon Contribution ...mentioning
confidence: 56%
See 3 more Smart Citations
“…For example, the turnover rate of the amino sugars was found to be faster under elevated CO 2 (Glaser et al, 2006). Secondly, our previous studies have confirmed enhanced plant root C input in warming plots, due to increased root growth/turnover and root exudation (Heinzle et al, 2023;Kengdo et al, 2022Kengdo et al, , 2023, indicating a shift in the balance of plant-versus microbial-derived SOM under climate warming.…”
Section: Warming Reduced the Microbial Necromass Carbon Contribution ...mentioning
confidence: 56%
“…(2022) and 2 Heinzle et al. (2023). Similarly, SOC content data is from studies conducted at the same site: 3 Tian, Schindlbacher, et al.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Elevated N deposition alters soil N availability for plants and microbes (Stevens et al., 2018; Figure 1). Because N is the primary limiting factor of plant productivity in terrestrial ecosystems, N promotion of plant growth likely enhances organic C for microorganisms that also transform more plant‐derived C into microbial residues (Ataka et al., 2020; Heinzle et al., 2023; Wang et al., 2022). Furthermore, N input can modify the composition of the soil microbial community, altering soil organic matter decomposition (Morrison et al., 2016).…”
Section: Introductionmentioning
confidence: 99%